A chip radiator with composite liquid metal and heat pipe
By adopting composite liquid metal and heat pipe design in the chip radiator, combined with graphene heat sink and L-shaped heat pipe, the problems of low heat dissipation efficiency and difficult to solve in the existing technology are solved, and efficient chip heat dissipation effect is achieved.
Patent Information
- Application Number
- CN202210184940.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-02-28
AI Technical Summary
The existing chip radiator has low heat dissipation efficiency, which is difficult to meet the development trend of high heat flow density and miniaturization, and it is difficult to solve local hot issues.
A chip radiator that uses composite liquid metal and heat pipes, uses the high unit volume latent heat and high thermal conductivity characteristics of liquid metal, combined with graphene heat sink and L-shaped heat pipes, quickly equalizes the chip surface temperature, and efficiently transfers heat to the outside world through the circulation flow of heat pipes and water vapor.
It significantly improves the heat exchange capacity of the chip radiator, shortens the phase change cycle of liquid metal, effectively alleviates local hot issues, and improves the operating efficiency of the radiator.
Smart Images

Figure CN114628342B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chip heat dissipation, and in particular to a chip heat sink composed of composite liquid metal and heat pipes. Background Art
[0002] With the rapid development of the electronics and semiconductor industries, various electronic chips are becoming increasingly miniaturized and integrated, and thermal barriers are becoming increasingly prominent. At the same time, due to the different functions of transistors within the chip, uneven heat flow is easily generated during actual operation, leading to the emergence of local hot spots on the chip. In actual chip operation, the local heat flux density can reach 10 to 1000 W·cm -2 , or even higher. The huge heat flux density can easily lead to chip performance degradation, greatly increase the probability of chip damage, and even cause safety accidents. Currently used chip heat sinks are mainly air cooling and heat pipe heat sinks. However, the heat dissipation capacity of air cooling and heat pipe technology is generally around 100 W·cm -2 The low heat dissipation efficiency and large size and mass make it difficult to meet the current trend of high heat flux and miniaturization, and it is difficult to solve the problem of local hot spots. Thermal barriers have become one of the main challenges hindering the development of higher performance electronic chips, and the development of high-performance chip cooling technology is urgent.
[0003] Phase change heat dissipation technology is one of the technologies that meet the development of miniaturization. It has the characteristics of small size and large heat absorption. This technology undergoes a phase change process with temperature changes, absorbing and releasing the heat emitted by the chip to achieve the purpose of chip temperature control. At present, the most widely used phase change materials are paraffin and other alkanes, with a melting point of 5-70℃ and a latent heat of fusion of 220-260kJ·kg -1 , thermal conductivity is 0.15 W·m -1 ·K -1 Alkane phase change materials such as paraffin wax have excellent phase change latent heat, but their thermal conductivity is low. The stability of organic matter decreases after repeated solidification and melting processes, and it is easy to precipitate during the phase change process. In addition, the temperature span between melting point and boiling point is small, which greatly limits its application.
[0004] To further improve the efficiency of chip phase change cooling technology, liquid metals, which offer low toxicity, a wide melting and boiling point range, excellent stability, large latent heat per unit volume, and high thermal conductivity, have emerged as a rapidly emerging cooling technology, replacing traditional paraffin and other hydrocarbon phase change materials. Typical types of liquid metals include gallium- and bismuth-based liquid metals, with melting and boiling point ranges typically exceeding 1000°C, latent heat per unit volume generally ranging from 200 to 600 kJ / L, and thermal conductivity two orders of magnitude higher than traditional paraffin, at 15 to 30 W·m -1 ·K -1, breaking the limits of traditional cooling technology capabilities. During the phase change process of liquid metal, not only does it absorb heat quickly and absorb a lot of heat, but the flow heat exchange after the liquid metal absorbs heat and changes into liquid state is conducive to alleviating local hot spot problems. It is suitable for chip thermal management occasions with high local heat flux density and compact size. Therefore, the research on applying liquid metal to chip heat sinks is of great significance. However, at this stage, the liquid metal phase change heat dissipation technology still has the following problems: in the early stage of liquid metal phase change, the liquid metal is solid, which is not conducive to balancing the surface temperature of the chip; the speed of releasing heat to the external environment during the phase change of liquid metal is slow, and there is a problem of long single cycle use time, which is not conducive to application in occasions with frequent work. Summary of the Invention
[0005] The present invention aims to address the defects of the prior art and provide a chip radiator composed of a composite liquid metal and a heat pipe, thereby solving the technical problem of low heat dissipation efficiency of the prior art chips.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A chip heat sink comprising a composite liquid metal and heat pipe comprises a shell and a heat pipe, wherein the middle portion of the heat pipe is disposed within the lower cavity of the shell. The heat sink further comprises a graphene heat sink, wherein the graphene heat sink utilizes SMT-035 graphene heat dissipation copper foil composed of 15μm graphene and 35μm copper foil. One side of the graphene heat sink is affixed to the bottom surface of the shell, and the chip is affixed to the other side of the graphene heat sink. The lower cavity is filled with liquid metal, wherein the liquid metal is a bismuth-based alloy, a gallium-based alloy, or an indium-based alloy. The heat pipe is an L-shaped heat pipe, wherein the distance from the horizontal section of the heat pipe to the bottom of the lower cavity is two-fifths of the height of the lower cavity. Fins are provided on the outside of the vertical section of the heat pipe, and the heat pipe is filled with water.
[0008] Furthermore, the heat pipes are made of copper pipes, the number of which is 5 to 11, and the pipe diameter is 2 to 4 mm, wherein the length of the horizontal section is 110 to 140 mm, and the height of the vertical section is 50 to 60 mm.
[0009] Furthermore, the shell is also provided with an upper cavity, in which a bipolar strong magnet is provided, and a motor is provided on the top of the shell, which is connected to the bipolar strong magnet through a drive shaft, and magnetic nanoparticles and SiO2 particles are added to the liquid metal.
[0010] Furthermore, the magnetic nanoparticles are nickel nanoparticles with a diameter of 50-100 nm and an addition amount of 5-10 wt %. The outer surface of the nickel nanoparticles is coated with SiO 2 with a thickness of 10 nm. The addition amount of the SiO 2 particles is 1 wt % and the particle size is 200 mesh.
[0011] Furthermore, a foam metal layer is provided on the inner wall surface of the lower cavity of the shell.
[0012] Furthermore, the foam metal layer is made of foam copper, with a porosity of 85% to 90%, an average pore diameter of 0.5 to 1 mm, and a thickness of 5 mm.
[0013] Furthermore, thermal grease is evenly filled between the shell and the graphene heat sink, and between the graphene heat sink and the chip, and the thickness of the thermal grease is 2 mm.
[0014] Furthermore, the fins are made of metal aluminum material with a thickness of 3 mm, and the shell is made of copper.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1) The present invention utilizes the phase change of liquid metal to absorb heat. The latent heat of phase change per unit volume of liquid metal is large, generally 200 to 600 kJ·L -1 About, and thermal conductivity> 15 W·m -1 ·K -1 , which is 2 orders of magnitude higher than water, can quickly and efficiently absorb the heat emitted by the chip, has a long stable time, and has excellent flow properties after phase change to liquid, which is conducive to alleviating local hot spot problems and effectively improving the heat exchange capacity of the radiator.
[0017] 2) The present invention uses SMT-035 graphene heat dissipation copper foil as a heat sink. This material has excellent lateral thermal conductivity and longitudinal thermal conductivity, can quickly equalize the surface temperature of the chip, and assists liquid metal phase change heat transfer technology to efficiently solve the local hot spot problem of the chip.
[0018] 3) Utilize liquid metal and heat pipe composite heat dissipation. The liquid metal is in direct contact with the heat pipe. After the liquid metal changes phase to liquid, it has excellent flow properties, which effectively reduces the contact thermal resistance. The heat absorbed by the liquid metal is quickly transferred to the heat pipe. The internal thermal resistance of the heat pipe is small and the thermal conductivity is excellent. Compared with metals such as copper and aluminum, the heat pipe per unit weight can transfer several orders of magnitude more heat. The water inside the heat pipe changes phase to water vapor when heated. The water vapor rises to the fin end to exchange heat with the outside world. After releasing heat, the water vapor changes phase to water and circulates driven by the density difference. The heat pipe quickly transfers the heat absorbed by the liquid metal to the outside world, shortening the phase change cycle of the liquid metal and further improving the heat exchange efficiency of the radiator.
[0019] 4) The present invention sets a magnetic drive device in the upper cavity of the shell, mixes magnetic nanoparticles in the liquid metal of the lower cavity, and utilizes the magnetic characteristics of the magnetic nanoparticles to apply disturbance to the liquid metal in the lower cavity, which helps to accelerate the condensation of the liquid metal. A foam metal layer is set on the inner wall of the lower cavity to increase the roughness of the wall to promote the condensation of the liquid metal. At the same time, the foam metal plays a role in enhancing heat transfer. At the same time, SiO2 with a mass percentage of 1wt% and a volume of 200 mesh is added to the liquid metal to reduce the supercooling of the liquid metal and further shorten the phase change period of the liquid metal.
[0020] 5) The present invention adopts a small-diameter L-shaped heat pipe (diameter of 3 to 10 mm), a heat pipe height of 20 to 60 mm, and fins made of aluminum material, which reduces the volume and mass of the radiator. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the three-dimensional structure of the present invention;
[0022] Figure 2 It is a side view of the structure of the present invention.
[0023] Figure 3 It is a side sectional view of the structure of the present invention.
[0024] Figure 4 It is a front sectional view of the structure of the present invention.
[0025] In the figure: 1-shell; 2-heat pipe; 3-fin; 4-chip; 5-water; 6-liquid metal; 7-thermal grease; 8-graphene heat sink; 9-foam metal layer; 10-bipolar strong magnet; 11-motor; 12-drive shaft; 13-lower cavity; 14-upper cavity. DETAILED DESCRIPTION
[0026] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0027] Example 1
[0028] A chip radiator of composite liquid metal and heat pipe comprises a shell 1, which contains an upper and lower cavity. A bipolar strong magnet 10 is arranged inside the upper cavity 14 of the shell 1, and the bipolar strong magnet 10 is connected to a drive shaft 12. The drive shaft 12 is connected to a motor 11 on the top of the shell 1. A graphene heat sink 8 is arranged on the bottom surface of the shell 1, and the graphene heat sink 8 fits the chip 4. Thermal conductive silicone grease 7 is evenly filled between the contact surface between the shell 1 and the graphene heat sink 8 and the contact surface between the graphene heat sink 8 and the chip 4. A foam metal layer 9 is provided on the inner wall surface of the lower cavity 13 of the shell 1, and the lower cavity 13 of the shell 1 is filled with liquid metal 6. The shell 1 also comprises a heat pipe 2, which passes through the lower cavity 13 of the shell 1 and is filled with water 5 for dissipating heat from the liquid metal 6. The heat pipe 2 is L-shaped, and fins 3 are arranged on the periphery of the vertical section of the heat pipe 2 for dissipating heat from the water 5.
[0029] In the above embodiment, the shell 1 is penetrated by the horizontal section of the heat pipe 2, and the distance between the heat pipe 2 and the bottom of the shell 1 is 2 / 5 of the height of the lower cavity 13. The shell 1 is made of copper and the cross-sectional size of the shell 1 is 3600mm. 2 , height 60mm, thickness 2mm. The cross-sectional area of the bipolar strong magnet 10 in the upper cavity 14 of the shell 1 is 500mm 2 , thickness is 10mm. Motor 11 adopts DC motor, uses 12V direct current.
[0030] The foam metal layer 9 in the lower cavity 13 of the housing 1 is made of foam copper, and the parameters of the foam copper are: porosity of 90%, average pore diameter of 0.5 mm, and thickness of 5 mm.
[0031] The graphene heat sink 8 uses SMT-035 graphene heat dissipation copper foil composed of 15μm graphene and 35μm copper foil, with a lateral thermal conductivity of 830 W·m -1 ·K -1 , the longitudinal thermal conductivity is 583 W·m -1 ·K -1 The cross-sectional dimensions of the graphene heat sink 8 are consistent with the cross-sectional dimensions of the housing 1, which is 3600 mm. 2 , thickness is 2mm.
[0032] Thermal grease 7 uses commercial thermal grease with a thermal conductivity of 8 W·m -1 ·K -1 , evenly filled between the contact surface between the shell 1 and the graphene heat sink 8 and the contact surface between the graphene heat sink 8 and the chip 4, with a thickness of 2 mm.
[0033] To prevent corrosion, heat pipe 2 is made of copper with a diameter of 3mm. There are 11 heat pipes 2. Heat pipe 2 is L-shaped, with a horizontal section length of 140mm and a vertical section height of 60mm. The connection between housing 1 and heat pipe 2 is secured by welding. Metal solder is added during the welding process to ensure a tight fit between the two, improving sealing and reducing contact thermal resistance. Fins 3 are made of aluminum and are 3mm thick.
[0034] Liquid metal 6 uses gallium-based alloy Ga 80 Sn 20 , melting point is 39℃, boiling point>1000℃, density is 5552kg·m -3 , the latent heat of phase change per unit volume is 607.4kJ·L -1 , heat capacity is 440J·kg -1 ·K -1 , the thermal conductivity is 16.7W·m -1 ·K -1 SiO2 with a mass percentage of 1 wt% and a size of 200 mesh is added to the liquid metal 6 to reduce the supercooling of the liquid metal 6. Magnetic nanoparticles are also added to the liquid metal 6. The magnetic nanoparticles are nickel nanoparticles with a diameter of 50 nm and a mass percentage of 10%. The outer surface of the magnetic nanoparticles is coated with SiO2 with a coating thickness of 10 nm.
[0035] At a heat flux of 500 W·cm -2 Under the condition of pulse time of 40ms, the surface temperature of the chip of this embodiment is 76℃ lower than that of the chip using traditional organic phase change wax, and the maintenance time is 3.3 times that of wax. The heat flow in the melting of wax is basically kept at 10 -1 W·cm -2 orders of magnitude, while liquid metal is as high as 10 1 W·cm -2 The heat absorption performance of this embodiment is 33.4 times that of traditional organic phase-change paraffin wax. The magnetic drive device, foam metal, and SiO2 in this embodiment effectively shorten the liquid metal phase change cycle, and the condensation time is shortened by 1.7 times compared to pure liquid metal.
[0036] Example 2
[0037] A chip radiator of a composite liquid metal and heat pipe comprises a shell 1, which contains an upper and lower cavity. A bipolar strong magnet 10 is arranged inside the upper cavity 14 of the shell 1, and the bipolar strong magnet 10 is connected to a drive shaft 12. The drive shaft 12 is connected to a motor 11 on the top of the shell 1. A graphene heat sink 8 is arranged on the bottom surface of the shell 1, and the graphene heat sink 8 fits the chip 4. Thermal conductive silicone grease 7 is evenly filled between the contact surface between the shell 1 and the graphene heat sink 8, and the contact surface between the graphene heat sink 8 and the chip 4. A foam metal layer 9 is provided on the inner wall surface of the lower cavity 13 of the shell 1, and the lower cavity of the shell 1 is filled with liquid metal 6. The shell 1 also comprises a heat pipe 2, which passes through the lower cavity 13 of the shell 1 and is filled with water 5 for dissipating heat from the liquid metal 6. The heat pipe 2 is L-shaped, and fins 3 are arranged on the periphery of the vertical section of the heat pipe 2 for dissipating heat from the water 5.
[0038] In the above embodiment, the shell 1 is penetrated by the horizontal section of the heat pipe 2, and the distance between the heat pipe 2 and the bottom of the shell 1 is 2 / 5 of the height of the lower cavity 13. The shell 1 is made of copper and the cross-sectional size of the shell 1 is 3600mm. 2 , height 60mm, thickness 2mm. The cross-sectional area of the bipolar strong magnet in the upper cavity of the shell 1 is 500mm 2 , thickness is 10mm. Motor 11 adopts DC motor, uses 12V direct current.
[0039] The foam metal layer 9 in the lower cavity 13 of the housing 1 is made of foam copper, and the parameters of the foam copper are: porosity of 85%, average pore diameter of 1.0 mm, and thickness of 5 mm.
[0040] The graphene heat sink 8 uses SMT-035 graphene heat dissipation copper foil composed of 15μm graphene and 35μm copper foil, with a lateral thermal conductivity of 830 W·m -1 ·K -1 , the longitudinal thermal conductivity is 583 W·m -1 ·K -1 The cross-sectional dimensions of the graphene heat sink 8 are consistent with the cross-sectional dimensions of the housing 1, which is 3600 mm. 2 , thickness is 2mm.
[0041] Thermal grease 7 uses commercial thermal grease with a thermal conductivity of 8 W·m -1 ·K -1 , evenly filled between the contact surface between the shell 1 and the graphene heat sink 8 and the contact surface between the graphene heat sink 8 and the chip 4, with a thickness of 2 mm.
[0042] To prevent corrosion, heat pipe 2 is made of copper with a diameter of 4mm. There are five heat pipes 2. Heat pipe 2 is L-shaped, with a horizontal section length of 140mm and a vertical section height of 60mm. The connection between housing 1 and heat pipe 2 is welded, with metal solder added during the welding process to ensure a tight fit, improve sealing, and reduce contact thermal resistance. The fins are made of aluminum and are 3mm thick.
[0043] Liquid Metal 6 uses bismuth-based alloy In 51 Bi 32.5 Sn 16.5 , melting point is 63℃, boiling point>1000℃, density is 8054kg·m-3, and latent heat of phase change per unit volume is 209kJ·L -1 , heat capacity is 220J·kg -1 ·K -1 , the thermal conductivity is 21.6W·m -1 ·K -1 1 wt% SiO2 with a size of 200 mesh was added to the liquid metal 6 to reduce the supercooling of the liquid metal 6. Magnetic nanoparticles were also added to the liquid metal 6. The magnetic nanoparticles were nickel nanoparticles with a diameter of 50 nm and a mass percentage of 5%. The outer surface of the magnetic nanoparticles was coated with SiO2 with a coating thickness of 10 nm.
[0044] At a heat flux of 500 W·cm -2 Under a pulse time of 40ms, the chip surface temperature of this embodiment is 24.5°C lower than that of a chip using traditional organic phase-change wax, and the temperature is maintained for 1.2 times longer than that of wax. The heat absorption performance of this embodiment is 11.5 times that of traditional organic phase-change wax. The magnetic drive device, metal foam, and SiO2 employed in this embodiment effectively shorten the liquid metal phase-change cycle, reducing the condensation time by 1.7 times compared to pure liquid metal.
[0045] Example 3
[0046] A chip radiator of composite liquid metal and heat pipe comprises a shell 1, which contains an upper and lower cavity. A bipolar strong magnet 10 is arranged inside the upper cavity 14 of the shell 1, and the bipolar strong magnet 10 is connected to a drive shaft 12. The drive shaft 12 is connected to a motor 11 on the top of the shell 1. A graphene heat sink 8 is arranged on the bottom surface of the shell 1, and the graphene heat sink 8 fits the chip 4. Thermal conductive silicone grease 7 is evenly filled between the contact surface between the shell 1 and the graphene heat sink 8 and the contact surface between the graphene heat sink 8 and the chip 4. A foam metal layer 9 is provided on the inner wall surface of the lower cavity 13 of the shell 1, and the lower cavity 13 of the shell 1 is filled with liquid metal 6. The shell 1 also comprises a heat pipe 2, which passes through the lower cavity 13 of the shell 1 and is filled with water 5 for dissipating heat from the liquid metal 6. The heat pipe 2 is L-shaped, and fins 3 are arranged on the periphery of the vertical section of the heat pipe 2 for dissipating heat from the water 5.
[0047] In the above embodiment, the shell 1 is penetrated by the horizontal section of the heat pipe 2, and the distance between the heat pipe 2 and the bottom of the shell 1 is 2 / 5 of the height of the lower cavity 13. The shell 1 is made of copper and the cross-sectional size of the shell 1 is 1600mm. 2 , height 50mm, thickness 2mm. The cross-sectional area of the bipolar strong magnet in the upper cavity 14 of the shell 1 is 300mm 2 , thickness is 10mm. Motor 11 adopts DC motor, uses 12V direct current.
[0048] The foam metal layer 9 in the lower cavity 13 of the housing 1 is made of foam copper, and the parameters of the foam copper are: porosity of 90%, average pore diameter of 0.5 mm, and thickness of 5 mm.
[0049] The graphene heat sink 8 uses SMT-035 graphene heat dissipation copper foil composed of 15μm graphene and 35μm copper foil, with a lateral thermal conductivity of 830 W·m -1 ·K -1 , the longitudinal thermal conductivity is 583 W·m -1 ·K -1 The cross-sectional dimensions of the graphene heat sink 8 are consistent with the cross-sectional dimensions of the housing 1, which is 1600 mm. 2 , thickness is 2mm.
[0050] Thermal grease 7 uses commercial thermal grease with a thermal conductivity of 8 W·m -1 ·K -1 , evenly filled between the contact surface between the shell 1 and the graphene heat sink 8 and the contact surface between the graphene heat sink 8 and the chip 4, with a thickness of 2 mm.
[0051] To prevent corrosion, heat pipe 2 is made of copper with a diameter of 2mm. There are nine heat pipes 2. Heat pipe 2 is L-shaped, with a horizontal section length of 110mm and a vertical section height of 50mm. The connection between housing 1 and heat pipe 2 is welded, with metal solder added during the welding process to ensure a tight fit, improve sealing, and reduce contact thermal resistance. The fins are made of aluminum and are 3mm thick.
[0052] Liquid Metal 6 uses bismuth-based alloy Bi 58 Sn 42 , melting point is 138℃, boiling point>1000℃, density is 8560kg·m -3 , the latent heat of phase change per unit volume is 383.5kJ·L -1 , heat capacity is 201J·kg -1 ·K -1 , the thermal conductivity is 19 W·m -1 ·K -1 SiO2 with a mass percentage of 1 wt% and a size of 200 mesh is added to the liquid metal 6 to reduce the supercooling of the liquid metal 6. Magnetic nanoparticles are also added to the liquid metal 6. The magnetic nanoparticles are nickel nanoparticles with a diameter of 100 nm and a mass percentage of 10%. The outer surface of the magnetic nanoparticles is coated with SiO2 with a coating thickness of 10 nm.
[0053] At a heat flux of 500 W·cm -2 Under a pulse time of 40ms, the chip surface temperature of this embodiment is 45°C lower than that of a chip using traditional organic phase-change wax, and the temperature is maintained for twice as long as that of wax. The heat absorption performance of this embodiment is 21.1 times that of traditional organic phase-change wax. The magnetic drive device, metal foam, and SiO2 employed in this embodiment effectively shorten the liquid metal phase-change cycle, reducing the condensation time by 1.8 times compared to pure liquid metal.
[0054] In the above-mentioned embodiments 1 to 3, the specific working principle of the chip heat sink of the composite liquid metal and heat pipe is as follows:
[0055] During operation, the uneven heat emitted by chip 4 is transferred to graphene heat sink 8 through heat conduction. Graphene heat sink 8 quickly equalizes this heat and transfers it to housing 1. Housing 1 transfers the heat to foam metal 9 in lower cavity 13. Liquid metal 6 is in direct contact with foam metal 9. Liquid metal 6 absorbs the heat from chip 4 and undergoes a phase change, first undergoing a latent heat phase change and then changing from a solid phase to a liquid phase. Liquid metal 6 is in direct contact with heat pipe 2 inside housing 1. Heat pipe 2 quickly absorbs the heat from the liquid metal, cools the liquid metal, and transfers the heat to water 5 inside heat pipe 2. The water 5 is heated and vaporizes into water vapor. Driven by the density difference, it rises to the end of fin 3. After transferring heat to the external environment, the water 5 is liquefied again and flows back to the contact section with the liquid metal for the next cycle. The motor 11 on the top of the shell 1 drives the drive shaft 12 to drive the bipolar strong magnet 10 to rotate, driving the magnetic nanoparticles in the lower cavity of the shell 1 to move, thereby disturbing the liquid metal 6 in the lower cavity 13 of the shell 1, accelerating the condensation of the liquid metal 6, and shortening the phase change cycle of the liquid metal 6. SiO2 is added to the liquid metal 6 to reduce the supercooling of the liquid metal 6, further shorten the phase change cycle of the liquid metal 6, and improve the operating efficiency of the radiator. Thermal conductive silicone grease 7 is filled between the shell 1 and the graphene heat sink 8 and between the graphene heat sink 8 and the chip 4 to reduce the contact thermal resistance. The shell 1, heat pipe 2 and foam metal 9 are all made of copper-containing materials to reduce the corrosion of the liquid metal to the shell 1, heat pipe 2 and foam metal 9. The heat pipe 2 is set to L-shaped to reduce the volume of the radiator. The fin 3 is made of aluminum material to reduce the mass of the radiator. Using gallium-based alloy Ga 80 Sn 20 、Bi-based alloy In 51 Bi 32.5 Sn 16.5 Or Bi 58 Sn 42 Liquid metal's high unit volume phase change latent heat and high thermal conductivity effectively improve the efficiency of the radiator in absorbing chip heat. Combining liquid metal, heat pipe and graphene heat sink, it can quickly equalize the chip surface temperature and efficiently transfer the heat generated by the heat source to the external environment to maintain the chip running at a lower operating temperature.
[0056] The above specific implementation methods are only for illustrating the technical concept and structural features of the present invention, and the purpose is to enable relevant persons familiar with this technology to implement them accordingly. However, the above content does not limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A chip heat sink of composite liquid metal and heat pipe, comprising a shell (1) and a heat pipe (2), wherein the middle portion of the heat pipe (2) is inserted into a lower cavity (13) of the shell (1), and characterized in that: It also includes a graphene heat sink (8), wherein the graphene heat sink (8) is made of SMT-035 graphene heat dissipation copper foil composed of 15 μm graphene and 35 μm copper foil, one side of the graphene heat sink (8) is attached to the bottom surface of the housing (1), and the chip (4) is attached to the other side of the graphene heat sink (8), and the lower cavity (13) is filled with liquid metal (6), and the liquid metal (6) is a bismuth-based alloy, a gallium-based alloy, or an indium-based alloy. The heat pipe (2) is an L-shaped heat pipe, the distance from the horizontal section of the heat pipe (2) to the bottom of the lower cavity (13) is two fifths of the height of the lower cavity (13), fins (3) are arranged on the outside of the vertical section of the heat pipe (2), the heat pipe (2) is filled with water (5), the heat pipe (2) is made of copper pipes, the number of which is 5 to 11, the pipe diameter is 2 to 4 mm, the length of the horizontal section is 110 to 140 mm, and the height of the vertical section is 50 to 60 mm; The housing (1) is further provided with an upper cavity (14), a bipolar strong magnet (10) is provided in the upper cavity (14), a motor (11) is provided on the top of the housing (1), and the motor (11) is connected to the bipolar strong magnet (10) via a drive shaft (12); The liquid metal (6) is added with magnetic nanoparticles and SiO2 particles. The magnetic nanoparticles are nickel nanoparticles with a diameter of 50-100 nm and an addition amount of 5-10 wt%. The outside of the magnetic nanoparticles is coated with SiO2 with a thickness of 10 nm. The addition amount of the SiO2 particles is 1 wt% and the particle size is 200 mesh.
2. A chip heat sink of composite liquid metal and heat pipe according to claim 1, characterized in that: A foam metal layer (9) is provided on the inner wall surface of the lower cavity (13) of the housing (1).
3. A chip radiator of composite liquid metal and heat pipe according to claim 2, characterized in that: The foam metal layer (9) is made of foam copper, has a porosity of 85% to 90%, an average pore diameter of 0.5 to 1 mm, and a thickness of 5 mm.
4. The chip radiator of composite liquid metal and heat pipe according to claim 1, characterized in that: Thermal conductive silicone grease (7) is evenly filled between the housing (1) and the graphene heat sink (8), and between the graphene heat sink (8) and the chip (4), and the thickness of the thermal conductive silicone grease (7) is 2 mm.
5. The chip radiator of composite liquid metal and heat pipe according to claim 1, characterized in that: The fins (3) are made of metal aluminum material and have a thickness of 3 mm, and the shell (1) is made of red copper.
Citation Information
Patent Citations
Graphene and liquid metal composite heat-dissipation method
CN104610925A
Cooling device resistant to heat flow impact
CN108195213A